2013
DOI: 10.1037/h0094743
|View full text |Cite
|
Sign up to set email alerts
|

Parents served by assertive community treatment: Parenting needs, services, and attitudes.

Abstract: Objective Assertive Community Treatment (ACT) is an evidence-based practice for individuals with severe mental illness. Although as many as half of all people with severe mental illness are parents, little is known about their experiences as parents and as recipients of mental health interventions, like ACT. The purpose of the current study was to examine the experiences of parent consumers served by ACT. Methods Seventeen parents being served by ACT teams were interviewed about parenting, parenting needs, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…Despite these high rates, few consumers reported having any custody of their children (23.2%), and most parents reported seeing their young children less than seven days per month. Consistent with previous research, few consumers with severe mental illness appear to have custody of their children, and those without custody may not see their children often (Gewurtz et al, 2004; Hearle et al., 1999; Joseph et al, 1999; White et al, 2013). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite these high rates, few consumers reported having any custody of their children (23.2%), and most parents reported seeing their young children less than seven days per month. Consistent with previous research, few consumers with severe mental illness appear to have custody of their children, and those without custody may not see their children often (Gewurtz et al, 2004; Hearle et al., 1999; Joseph et al, 1999; White et al, 2013). …”
Section: Discussionsupporting
confidence: 82%
“…Because parents reported lower preferences for autonomy and less activation in treatment, parents may need additional assistance with regard to parenting-specific issues and unmet needs (Brunette & Dean, 2002; Nicholson & Biebel, 2002; Nicholson et al, 2001; White et al., 2013), but may also need greater support in managing mental health conditions on top of the demands of being a parent. For example, it may be helpful to integrate illness management training with parenting programs.…”
Section: Discussionmentioning
confidence: 99%
“…, White et al . , Cook & Mueser ). Most recently Aldersey & Whitley () conducted a study on the role of family members on recovery and found that, apart from practical support, the family also may give moral support and functions as a motivation for recovery.…”
Section: Discussionmentioning
confidence: 98%
“…), assessment of their needs (Howard & Underdown ), and the development and evaluation of programmes (White et al . ). However, not much is known about the way these mothers and fathers come to grips with challenges in their parental role or about the meaning of parenting in their recovery processes.…”
Section: Introductionmentioning
confidence: 97%
“…Reports on the help-seeking behaviour among seriously ill parents regarding parental problems indicate that parents with substance abuse problems and mental illness are reluctant to seek such help. For some, this is because they are afraid of losing their parental rights [6, 7]. Studies from the UK and Norway have found that parents with serious mental health problems often do not receive help in order to support their children [1, 8, 9].…”
Section: Introductionmentioning
confidence: 99%